2016
DOI: 10.1002/mma.3882
|View full text |Cite
|
Sign up to set email alerts
|

On regularity criterion to the 3D axisymmetric incompressible MHD equations

Abstract: This paper is concerned with the regularity criterion for a class of axisymmetric solutions to 3D incompressible magnetohydrodynamic equations. More precisely, for the solutions that have the form of u D u r e r C u  e  C u z e z and b D b  e  , we prove that if jru.x, t/j Ä C holds for 1 Ä t < 0, then .u, b/ is regular at time zero. This result can be thought as a generalization of recent results in for the 3D incompressible Navier-Stokes equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Liu et al. [34] established some regularity criteria for a class of axisymmetric solutions to the 3D incompressible MHD equations with magnetic field of particular form, similar research made for the axisymmetric MHD equations can be found in [24, 45, 47, 54] and references therein.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…Liu et al. [34] established some regularity criteria for a class of axisymmetric solutions to the 3D incompressible MHD equations with magnetic field of particular form, similar research made for the axisymmetric MHD equations can be found in [24, 45, 47, 54] and references therein.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%